2005
DOI: 10.1080/08035250500252872
|View full text |Cite
|
Sign up to set email alerts
|

Graves' disease in children and adolescents: Response to long‐term treatment

Abstract: Implementation of a long-term antithyroid drug protocol achieved 40% long-term remissions in paediatric patients with Graves' disease. Need for maintained high doses of antithyroid drugs could be considered a predictive factor for no remission. When permanent remission was not obtained by medical treatment, I(131)and/or surgery allowed healing in all cases.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
8

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(24 citation statements)
references
References 32 publications
0
15
0
8
Order By: Relevance
“…Twenty-one trials (1,239 patients) used ATD as intervention [1, 5, 7-9, 12, 17, 18, 22, 23, 27, 28, 31-34, 36, 39, 40, 49, 51], of which five (207 patients) were published in Chinese. Twenty-five trials (1,362 patients) used thyroidectomy as intervention [2,4,5,7,11,18,23,28,30,33,37,38,49,53,56,57,[61][62][63][64][65][66][67][68]70], of which 13 (681patients) were published in Chinese. The follow-up periods were from 1 to 36 years.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Twenty-one trials (1,239 patients) used ATD as intervention [1, 5, 7-9, 12, 17, 18, 22, 23, 27, 28, 31-34, 36, 39, 40, 49, 51], of which five (207 patients) were published in Chinese. Twenty-five trials (1,362 patients) used thyroidectomy as intervention [2,4,5,7,11,18,23,28,30,33,37,38,49,53,56,57,[61][62][63][64][65][66][67][68]70], of which 13 (681patients) were published in Chinese. The follow-up periods were from 1 to 36 years.…”
Section: Results Of Searchmentioning
confidence: 99%
“…Estos últimos suelen asociar menores efectos adversos, sin embargo, a excepción de la Clozapina, también se asocian a disquinesia tardía. (12,13) En niños se han utilizado risperidona y olanzapina a partir de los 12 años de edad. Estos tienen menor efecto sedante que los neurolépticos tradicionales como el Haloperidol, Flufenazina, Tioridazina y Clorpromazina.…”
Section: Discussionunclassified
“…Remission is achieved in less than 30% of children after a first course of ATD for about 2 years (18). In children, studies have shown that a longer initial duration of euthyroid state with ATD is associated with a lower risk of relapse after a first course of ATD therapy (18,19).…”
Section: No1 February 2013mentioning
confidence: 99%
“…It suggested that children with Graves' disease who display good compliance with treatment and with no major adverse effects of ATD may be offered up to 8-10 years of medical treatment before definitive treatment is considered (20). As with studies done in adults, long term therapy with carbimazole/ methimazole has been shown to be safe without any major adverse effects (19,20).…”
Section: No1 February 2013mentioning
confidence: 99%